Plant training systems for the peach cultivar Della Nona - Giacobbo, Clevison Luiz; Prado, Jean do; Uberti, Alison; Lugaresi, Adriana; Fischer, Lucas Lobato de Oliveira (Scientific Electronic Archives, 2024)
Cultivation of stone fruit trees in many producing countries is traditionally carried out with low planting density and training in open plant systems (pots). However, the higher density systems and training with more compact mills, for example the 'leading system', have been providing better production. The objective of this work was to evaluate the phenological, vegetative, and productive characteristics of the peach cultivar Della Nona, subjected to various training systems. The work was conducted during two production cycles where three driving systems were evaluated: 'central leader' (5.0 m x 0.8 m, 2,500 plants ha-1), 'Y shape' (5.0 m x 1.5 m, 1,333 plants ha-1) and 'vase' (5.0 m x 3.5 m, 571 plants ha-1). We showed that phenological development was not influenced by the different training systems. The training system 'central leader' gave lower cup size, lower production, but higher productivity. We conclude that the 'central leader' training system adapts to the conditions of the region and shows high productivity for the peach cultivar Della Nona.